2001
DOI: 10.1063/1.1357955
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory testing of the Mini-Magnetospheric Plasma Propulsion (M2P2) prototype

Abstract: Mini-Magnetospheric Plasma Propulsion (M2P2) seeks the creation of a magnetic wall or bubble (i.e. a magnetosphere) attached to a spacecraft that will intercept the solar wind and thereby provide high-speed propulsion with little expenditure of propellant. Results from a laboratory prototype that demonstrate the basic formation and expansion of a mini-magnetosphere are presented. The prototype uses a helicon source embedded asymmetrically in a dipole-like magnetic field. Breakdown of the plasma can be produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…This propulsion system, illustrated in Fig.18, is called mini-magnetospheric plasma propulsion (M2P2) or MagnetoPlasma Sail (MPS). This idea gained great interest because the study by Winglee et al (Winglee, et al, 2001) suggested the possibility of dramatically large acceleration by M2P2 spacecraft in deep space.…”
Section: The Principle Of M2p2 and Magnetoplasma Sailmentioning
confidence: 99%
See 1 more Smart Citation
“…This propulsion system, illustrated in Fig.18, is called mini-magnetospheric plasma propulsion (M2P2) or MagnetoPlasma Sail (MPS). This idea gained great interest because the study by Winglee et al (Winglee, et al, 2001) suggested the possibility of dramatically large acceleration by M2P2 spacecraft in deep space.…”
Section: The Principle Of M2p2 and Magnetoplasma Sailmentioning
confidence: 99%
“…The first experiment on the magnetic field inflation concept was tried by Winglee and his group (Winglee, et al, 2001;Ziemba, et al, 2001;Slough, et al, 2001;Giersch, et al, 2003). A highdensity helicon or an arc plasma source is located in a drum-like solenoid to observe magnetic field inflation.…”
Section: Preliminary Experiments Of M2p2/mpsmentioning
confidence: 99%
“…The set up of the simulations at the inner boundary is shown in Figure 1, and closely models the actual laboratory kW prototype 4,5 . A dipole magnet represented by a hollow (black/white) cylinder with a radius of 20 cm.…”
Section: Simulation Modelmentioning
confidence: 99%
“…It is sufficient for example to produce differential erosion of surface material of Ganymede 1 and for the erosion of the Martian atmosphere 2 . At the same time there is potential for harnessing the solar wind for enhanced spacecraft propulsion, as suggested in MiniMagnetospheric Plasma Propulsion (M2P2) 3,4 . In this scheme a magnetic field attached to the spacecraft is expanded by the injection of plasma to a scale size of the order of 10 km.…”
Section: Introductionmentioning
confidence: 99%
“…The M2P2 concept attempts to couple with the ambient solar wind to provide an overall power efficiency gain >> 1 with thrust levels predicted by simulation of several Newtons. 6 To accomplish this, plasma must be produced and injected along an imposed dipole magnetic field as has been previously described. 7 Plasma parameters required for the M2P2 concept are similar to those produced by helicon plasma sources.…”
Section: Introductionmentioning
confidence: 99%